A Historical Earthquake-Induced Landslide Damming Event at the Qiaojia Reach of the Jinsha River, SE Tibetan Plateau: Implication for the Seismic Hazard of the Xiaojiang Fault - Hu, Mengmeng; Wu, Zhonghai; Reicherter, Klaus; Ali, Sajid; Huang, Xiaolong; Zuo, Jiameng (Frontiers in Earth Science, 2021)
In bedrock mountainous areas where active faults and deep river valleys interact, earthquake-induced landslides can be used to explore local seismic hazards. The intersection of the highly active Xiaojiang Fault and the Jinsha River and its main tributaries in southwest China is a site of abundant earthquake-induced landslides. We found a suspected earthquake-induced landslide in the Qiaojia reach of the Jinsha River, where the Qiaojia Segment of the Xiaojiang Fault passes through. A high-resolution Digital Surface Model (DSM) generated from Unmanned Arial Vehicle (UAV) images and field investigations were used to confirm the existence of the landslide and analyze its characteristics. It is proven that a failed slope collapsed as a rock fall cluster at the west bank of the Jinsha River. We dated the failed slope collapse with the related dammed lake sand using the OSL and 14C dating methods. It showed a good temporal coincidence with the 624 AD earthquake. Combined with the characteristics of the depositional extent and spatial relevance between this collapse and the Qiaojia Segment, we concluded its seismic origin. Moreover, the 624 AD earthquake was reanalyzed for its magnitude and macro-epicenter, which was calculated to Mw7.7 or Ms7.9 and relocated to the Qiaojia area. No M ≥ 7 earthquakes have occurred on the Qiaojia Segment for nearly 1400 years since 624 AD. The elapsed time has exceeded the average recurrence interval of large earthquakes on the Xiaojiang Fault or the Qiaojia Segment. Therefore, the seismic hazard of the Qiaojia area should be considered in the future.